The impact of post-exercise hydration with deep-ocean mineral water on rehydration and exercise performance - Keen, D. A.; Constantopoulos, E.; Konhilas, J. P. (Journal of the International Society of Sports Nutrition, 2016)
Dehydration caused by prolonged exercise impairs thermoregulation, endurance and exercise performance. Evidence from animal and human studies validates the potential of desalinated deep-ocean mineral water to positively impact physiological and pathophysiological conditions. Here, we hypothesize that deep-ocean mineral water drawn from a depth of 915 m off the Kona, HI coast enhances recovery of hydration and exercise performance following a dehydrating exercise protocol compared to mountain spring water and a carbohydrate-based sports drink.